The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1080/02670836.2022.2130527
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performances of CuSn10Bi3 alloy containing MoSi2 and ferrophosphorus under starved lubrication

Abstract: The effects of molybdenum disilicide (MoSi2) and ferrophosphorus (FemPn) particles on the tribological properties of copper-tin bismuth (CuSn10Bi3) bimetallic bearing materials were studied in this paper. The samples of CuSn10Bi3 containing MoSi2 and/or FemPn were prepared by powder sintering technology and the metallographic structure of four kinds of self-lubricating copper alloy composite materials after sintering was observed. The tribological properties of the copper alloy composites under starved lubrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Zhao et al [7] studied that the CoF of copper alloy under boundary lubrication was 0.208 at a load of 10 N and a reciprocating speed of 600 rpm. Yang et al [8] introduced the CoF of CuSn10Bi3 which was up to 0.18 under specific conditions (e.g., load 100 N, sliding speed 6.1 m/s and boundary lubrication). The aforementioned studies have revealed that the CoF is high where the copper alloy surface is under boundary lubrication and dry sliding wear.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [7] studied that the CoF of copper alloy under boundary lubrication was 0.208 at a load of 10 N and a reciprocating speed of 600 rpm. Yang et al [8] introduced the CoF of CuSn10Bi3 which was up to 0.18 under specific conditions (e.g., load 100 N, sliding speed 6.1 m/s and boundary lubrication). The aforementioned studies have revealed that the CoF is high where the copper alloy surface is under boundary lubrication and dry sliding wear.…”
Section: Introductionmentioning
confidence: 99%
“…Using special lubrication methods or additives can effectively reduce the friction coefficient and friction losses of rolling bearings, providing good lubrication effects and prolonging the service life of bearings. Among these, materials such as solid paraffin (Dawari et al , 2022), hydrogenated diamond-like carbon coatings (Zhou et al , 2022), titanium alloys (Zhao et al , 2022a), self-lubricating polymer composites (Rodiouchkina et al , 2022; Zhao et al , 2022b), molybdenum disulfide and its composites (Yang et al , 2023; Gokce et al , 2021; Yang et al , 2022; Bhardwaj et al , 2021), polytetrafluoroethylene (PTFE) composites (Gungor and Demirer, 2022; Beckford et al , 2011; Deleanu and Georgescu, 2015; Feng et al , 2021; Lin et al , 2021; Trabelsi et al , 2016), graphene materials (Jin et al , 2023; Mao et al , 2018; Wu et al , 2021a; Jin et al , 2021) and alumina (Al 2 O 3 ) composites (Zhang et al , 2016; He et al , 2020; Tong et al , 2022) have demonstrated excellent anti-wear performance and tribological characteristics. However, the method of storing composite solid lubricants in bearing grooves has yet to receive attention.…”
Section: Introductionmentioning
confidence: 99%